2003
DOI: 10.1002/bem.10112
|View full text |Cite
|
Sign up to set email alerts
|

Occupational magnetic field exposures of garment workers: Results of personal and survey measurements

Abstract: To explore the feasibility of performing an epidemiologic study of female breast cancer and magnetic field (MF) exposures, we chose to study garment workers, who reportedly have some of the highest MF exposures. We collected personal exposure (PE, n = 48) and survey measurements (n = 77) near commercial sewing machines at three garment facilities and conducted a pilot interview among 25 garment workers asking about exposure duration, activities, and machine characteristics. MF levels were higher for older mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Our findings support the conclusion of Kelsh et al [2003], that the age of a sewing machine is a general attribute that may strongly correlate with various technical developments over the years. Newer machines are perhaps more efficient, require less power, and thus lower current than older ones, and exhibit lower MFs.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings support the conclusion of Kelsh et al [2003], that the age of a sewing machine is a general attribute that may strongly correlate with various technical developments over the years. Newer machines are perhaps more efficient, require less power, and thus lower current than older ones, and exhibit lower MFs.…”
Section: Discussionsupporting
confidence: 90%
“…Estimated mean daily times of usage of home sewing machines were 17 min. Kelsh et al [2003] found that the measured differences in field levels between sewing and idling (the machine was on, but not being used) conditions were not significant. The mean survey measurements, averaged over all body locations, at 60 Hz for AC machines were 1.71 and 1.22 mT for a sewing machine shop and a sample facility.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations